2021
DOI: 10.1002/sctm.20-0394
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived regenerative cells and lipotransfer in alleviating breast cancer-related lymphedema: An open-label phase I trial with 4 years of follow-up

Abstract: Patients with breast cancer-related lymphedema (BCRL) have reduced quality of life and arm function. Current treatments are palliative, and treatments improving lymphedema are lacking. Preclinical studies have suggested that adipose-derived regenerative cells (ADRCs) can alleviate lymphedema. We, therefore, aimed to assess whether ADRCs can alleviate lymphedema in clinical reality with long-term follow-up. We treated 10 patients with BCRL using ADRCs and a scar-releasing lipotransfer to the axillary region, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…This may explain the inconsistent treatment results observed after microsurgical and physiotherapeutic lymphedema treatments 25 29 . Regardless, future studies are needed to elucidate whether the excess amounts of volume, fat and lean mass can predict which patients are more likely to benefit from selective BCRL treatments 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the inconsistent treatment results observed after microsurgical and physiotherapeutic lymphedema treatments 25 29 . Regardless, future studies are needed to elucidate whether the excess amounts of volume, fat and lean mass can predict which patients are more likely to benefit from selective BCRL treatments 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment codes for physiotherapeutic lymphedema treatment were used to confirm the diagnosis of BCRL and were retrieved from all hospitals in the region of southern Denmark or outside hospitals from referred BCRL patients. Identified patients with BCRL were further evaluated clinically in our Plastic Surgery subunit for surgical lymphedema treatment for: (21) duration of BCRL, (22) severity of BCRL using multiple circumference measurements to estimate limb volume 29,30 , (23) clinical BCRL stage 31 and (24) current use of BCRL treatment. Incomplete or inconsistent information regarding BCRL diagnosis was supplemented by review of the electronic medical records.…”
Section: Participantsmentioning
confidence: 99%
“…Although no adverse effects related to cancer have been observed, the potential risk of cancer recurrence of using stem cells in the treatment of secondary lymphedema should be studied. A recently published Phase I study has found no evidence of breast cancer recurrence at 4-year follow up [ 58 ]. However, to further substantiate this relevant safety concern, a greater number of patients must be followed up longer-term in randomized clinical studies to formally rule out any contribution of stem cell transplants to cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%